THE KHäILAMA AND ARYSKAN MASSIFS OF ALKALI GRANITOIDS, EASTERN SAYAN: AGE AND FORMATION CONDITIONS BY RB-SR ISOTOPIC AND GEOCHEMICAL DATA - Kostitsyn Yu.A.; Altukhov E.N. (My University, 2004)
The paper includes new data on alkali granites of the Khäilama massif comprising the Zashikhinskoe rare-metal deposit (Eastern Sayan) and on metasomatites of the Aryskan rare-metal deposit (northeastern Tuva) and barren Astyg and Aksug alkali granite massifs probably genetically related to the Aryskan deposit. A Rb-Sr isochron determining the age of 261 ± 4 Ma and initial Sr isotopic ratio of 0.703 ± 11 (MSWD = 1) was obtained by six samples of alkali granites of the Khäilama massif. The point corresponding to a metasomatically altered (albitized) sample only deviates insignificantly from the isochron, which cannot indicate any notable difference between the ages of magmatic and metasomatic processes. The Aryskan ore-bearing metasomatites have not determined an isochron. They probably followed the magmatic process at about 455 m. y. ago. About 340 Ma ago, the Rb-Sr isotopic system of these rocks, as well as the Astyg and Aksug granitoids, was disturbed by stress-related recrystallization. Alkali granitoids of northeastern Tuva originated in an environment of intracontinental rifting. The formation of the Khäilama massif was related to anorogenic magmatism in Central Asia. An analysis of these Rb-Sr data and some published examples show that the isochron sensu stricto composed by magmatic rocks without any traces of hydrothermal metasomatic or metamorphic alteration corresponds to the age of magmatic process. The distance between sampling sites should be large enough to ensure the absence of Rb and Sr diffusion between the sampled areas.